Estudio de factibilidad para la creación de una agencia de publicidad Below The Line en la ciudad de Quito - Montaño Esparza, Grace Jacqueline (2013)
This document is divided into six chapters that address the problem of "Feasibility study for the creation of an advertising agency Below The Line in the city of Quito". Chapter I shows an overview of the study, which includes the issues, and other aspects of the resolution of the same, as are the theoretical framework and the research methods used. Forward Chapter II briefly reviews the national advertising market, which analyzes the factors involved in the development of this industry. To determine the target market Chapter III highlights the research methodology applied to the same, that through the analysis of data from surveys has gotten quantify the unmet and thus the market share that the company expected.